The Effect of Using Pegagan Leaves (Centella Asiatica L. Urban) Extract on The Physical Properties and Antioxidant Capacity of Mochi Ice Cream - Ummi Rohajatien; Laili Hidayati; Yeri Ayu Safitri (Bulletin of Culinary Art and Hospitality, 2022)
Pegagan leaf is a popular medicinal plant widely found in Indonesia. Pegagan can also be used in food and beverage products, such as mochi ice cream. This study aims to determine the physical properties (color and textures) and antioxidant capacity of mochi ice cream with different pegagan leaf extract concentrations of 20, 30, and 40 percent. This experimental study used a CRD (Completely Randomized Design), with treatment carried out twice for each concentration. The data obtained were analyzed using a one-way ANOVA (Analysis of Variance) test. If a real difference was observed, then the DMRT (Duncan's Multiple Range Test) was carried out. The results showed that the highest color brightness (L) mochi ice cream was obtained from a 20 percent concentration of pegagan leaf extract. The highest level of greenish color (a-) was obtained from 40 percent pegagan leaf extract, while the highest level of yellowish color (b+) was obtained from 20 percent pegagan leaf extract. The highest textures was obtained from a concentration of 20 percent pegagan leaf extract, and the highest antioxidant capacity was obtained from 40 percent pegagan leaf extract. Therefore, pegagan leaf extract concentration affects mochi ice cream's color, textures, and antioxidant content.